Representasi Aktor Sosial dalam Pemberitaan Kasus Polwan Bakar Suami: Analisis Wacana Kritis - Mubarok, Hamim; Cahyono, Arik Fajar (Icon: Islamic Communication and Contemporary Media Studies, 2025)
This study aims to examine the representation of social actors in the coverage of the “Policewoman Burns Husband” case published by the online news outlets Kompas.com and Liputan6.com using Theo van Leeuwen’s Critical Discourse Analysis (CDA) framework. Employing a descriptive qualitative approach, the study analyzes how meaning is constructed in news discourse through strategies of exclusion and inclusion, particularly in the forms of activation and passivation of social actors. The data consist of online news articles published between June and August 2024. The findings reveal that Kompas.com tends to represent the perpetrator as an active and personalized social actor through explicit identification and the use of emotionally charged narratives, thereby positioning the individual at the center of the discourse. In contrast, Liputan6.com predominantly employs passive and impersonal constructions by emphasizing legal-formal aspects and the role of law enforcement institutions, while downplaying the emotional dimensions of individual actors. These differences in representational strategies reflect distinct media ideologies and social constructions in framing the same event, highlighting the role of media discursive practices in shaping public perceptions of social actors and power relations in cases of domestic violence.